Uncovering a new mechanism of ischemic stroke: a study of the association between γδ T cells and immunoinflammation - Sun, Xuan; Wang, Jiayan; Gu, Hao; Guo, Maojuan; Yang, Zhen (Frontiers in Immunology, 2025)
Ischemic stroke, characterized by high clinical mortality and poor prognosis, has been prioritized by the World Health Organization (WHO) for reducing the burden of non-communicable diseases. However, the pathogenesis of ischemic stroke remains complex and poorly understood. Recent studies have revealed the infiltration of γδ T cells within ischemic stroke lesions, accompanied by the upregulation of IL-17, IL-23, and other inflammatory cytokines, suggesting their involvement in the stroke’s pathological process. Literature indicates that γδ T cells are recruited to the lesion site by microglia-derived chemokines and subsequently infiltrate the damaged brain tissue. This review summarizes current knowledge on the precise mechanisms underlying γδ T cell activation, migration, and ensuing immune-inflammatory responses in neuroinflammation, as well as their role in the progression of ischemic stroke. It further discusses the therapeutic potential of targeting γδ T cells to modulate neuroinflammation for ischemic stroke treatment, thereby offering novel therapeutic targets for managing neuroinflammation in this condition.